PENGARUH IKLIM SEKOLAH, LINGKUNGAN DAN KEPUASAN TERHADAP KINERJA GURU KELAS SD NEGERI SE-KECAMATAN JANGKA KABUPATEN BIREUEN - Nuraini, Nuraini; Ilyas, Mohd. (IndOmera, 2021)
The study was conducted on 70 elementary school teachers, with the aim of determining; A. the influence of school climate on teacher performance, b. the influence of the work environment on teacher performance, c. the effect of job satisfaction on teacher performance, and d. the influence of school climate, work environment and job satisfaction simultaneously on the performance of elementary school teachers. The study took the object of elementary school (SD) class teachers in the Jangka District, Bireuen Regency - Aceh, with a sample of 70 people as research respondents. The research method is associative with quantitative data. While the analytical approach uses path analysis. The results showed that a) school climate factors affect teacher performance by 22.69%, b) school environment factors affect teacher performance by 12.78%, 3) Job satisfaction factors affect teacher performance by 13.57%. 4) And the simultaneous influence of school climate, work environment and teacher job satisfaction of 48.3% on the performance of elementary school teachers in Jangka District, Bireuen Regency